2013
DOI: 10.1108/00330331311313726
|View full text |Cite
|
Sign up to set email alerts
|

Open source solutions for libraries: ABCD vs Koha

Abstract: Abstract:Purpose -The purpose of this study is to present an overview of the two open source (OS) integrated library systems (ILS) -Koha and ABCD (ISIS family), to compare their "next-generation library catalog" functionalities, and to give comparison of other important features available through ILS modules.Design/methodology/approach -Two open source ILSs, Koha and ABCD, were compared in-depth according to their functionalities and characteristics. A checklist was created for each module: acquisition, catalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…The author concludes that it offers a nice solution for all types of modern 229 DL and collection management tools libraries to meet the ever-increasing needs of users when library budget is on the decline. Another study compares in-depth Koha and ABCD according to their functionality and characteristics (Macan et al, 2013). This evaluation revealed that Koha has more functionalities than ABCD, especially those connected with the "next generation library catalog."…”
Section: Prog 493mentioning
confidence: 99%
“…The author concludes that it offers a nice solution for all types of modern 229 DL and collection management tools libraries to meet the ever-increasing needs of users when library budget is on the decline. Another study compares in-depth Koha and ABCD according to their functionality and characteristics (Macan et al, 2013). This evaluation revealed that Koha has more functionalities than ABCD, especially those connected with the "next generation library catalog."…”
Section: Prog 493mentioning
confidence: 99%
“…There are, however, disadvantages to OS ILS, in particular, the need for in-house IT expertise. Although Macan et al (2013) are optimistic, stating that "increased functionalities and better manuals" could mitigate for a lack of dedicated IT staff in libraries, the use of OS ILS requires sufficient technical expertise to perform the installation and migration of data, modify source code in order to customize features and functionalities based on libraries' needs, ongoing troubleshooting and maintenance (Bilal, 2014;Webber and Peters, 2010). Most OS ILS have vibrant user communities that can provide support although a timely response is not guaranteed.…”
Section: Introductionmentioning
confidence: 99%
“…In a thorough comparative evaluation, Koha outperformed or matched NewGenLib in many of the aspects evaluated (Singh and Sanaman, 2012) although Müller (2010) earlier rejected NewGenLib in his study for lack of adequate community involvement and support. Macan et al (2013) found that, although Koha has more functionalities, ABCD, which is derived from ISIS, is worth considering by libraries without IT support. In a study comparing Koha and Evergreen with two proprietary ILS, Pruett and Choi (2013) found that both Koha and Evergreen are viable alternatives to major proprietary vendors; these two OS ILS are the most popular in the USA (Singh, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Mavodza gives a very detailed analysis of cloud computing and Software as a Service (SaaS), and the benefits, tradeoffs, and caveats that libraries need to consider (Mavodza, 2013). Hadro (2009), Macan (2013), and Dalling and Rafferty (2013), discuss pros and cons of open-source computing, which is an attempt by companies to develop more flexible and more affordable software for libraries. This trend does not seem to be gaining much traction with libraries but is definitely an important force in the computing environment.…”
Section: Computing Environmentmentioning
confidence: 98%